Global Water Transfer Megaprojects: A Potential Solution for the Water-Food-Energy Nexus? - Shumilova, Oleksandra; Tockner, Klement; Thieme, Michele; Koska, Anna; Zarfl, Christiane (Frontiers in Environmental Science, 2018)
Globally, freshwater is unevenly distributed, both in space and time. Climate change, land use alteration, and increasing human exploitation will further increase the pressure on water as a resource for human welfare and on inland water ecosystems. Water transfer megaprojects (WTMP) are defined here as large-scale engineering interventions to divert water within and between river basins that meet one of the following criteria: construction costs > USD 1 billion, distance of transfer > 190 km, or volume of water transferred exceeds 0.23 km3 per year. WTMP represent an engineered solution to cope with water scarcity. These projects are most commonly associated with large-scale agricultural and energy development schemes, and many of them serve multiple purposes. Despite numerous case studies that focus on the social, economic and environmental impacts of individual water transfer megaprojects, a global inventory of existing, planned and proposed projects is lacking. We carried out the first comprehensive global inventory of WTMP that are planned, proposed or under construction. We collected key information (e.g. location, distance, volume, costs, purpose) on 34 existing and 76 future (planned, proposed or under construction) WTMP. If realized, the total volume of water transferred by future projects will reach 1,910 km3 per year with a total transfer distance of more than twice the length of the Earth’s equator. The largest future WTMP are located in North America, Asia and Africa and the predicted total investment will exceed 2.7 trillion US$. Among future projects, 42 are for agricultural development, 13 for hydropower development and 10 combine both purposes. Future megaprojects are also planned to support mining, ecosystem restoration and navigation. Our results underscore the extent to which humans have and are planning to re-engineer the global hydrological network and flows through WTMP, creating a network of “artificial rivers”. They emphasize the need to ensure the inclusion of these projects in global and basin hydrological models, and to develop internationally agreed criteria to assess the ecological, social and economic impacts of WTMP.